Peran Aktivis Pers Mahasiswa Jawa Tengah dalam Meluaskan Internet Damai - Amelia Rahmi; Qorby Haqqul Adam (Jurnal Riset Jurnalistik dan Media Digital, 2022)
Abstract. Symptoms of hoax information show the character of the information society that has not been properly educated. The massive spread of hoax indicates the lack of civility of a society and can cause division or slander in the pluralistic Indonesian nation. All components of society need to contribute to suppressing the spread of hoaxes, and it is important to build a healthy information climate to unite this great nation. Whatever the students press activists in Central Java, who have been affected by hoaxes are interesting and important to study considering that they are prospective journalists who are required to have strong journalistic commitment and skills. What role can students press activists play in creating a peaceful internet? The study was conducted at eight state universities in Central Java, involving 78 respondents. Data were collected by questionnaire and then performed multiple regression analysis. To expand the peaceful internet among the wider community or within campuses, the role of student pers activists can be carried out in forms such as: broadcasting news responsibly, sourcing credible news sources, providing assistance to youth/ peers. The student press has a great opportunity to voice a peaceful internet, encouraging readers to be more concerned about the fate and future of the naturally plural Indonesian nation to continue to be united in a single diversity. Abstrak. Gejala informasi hoaks menunjukkan ciri khas belum teredukasinya sebuah masyarakat informasi dengan baik. Menyebarnya hoaks secara massif mengindikasikan kurang beradabnya suatu masyarakat, dan dapat menimbulkan perpecahan ataupun fitnah pada bangsa Indonesia yang plural. Semua komponen masyarakat perlu andil menekan penyebaran hoaks, dan penting membangun iklim informasi yang sehat untuk menyatukan bangsa yang besar ini. Apakah aktivis Pers (pers) Mahasiswa (mahasiswa) yang berada di Jawa Tengah telah terpengaruh hoaks menarik dan penting dikaji mengingat mereka merupakan calon wartawan yang dituntut memiliki komitmen dan keterampilan jurnalistik yang kuat. Bagaimana peran yang dapat dilakukan aktivis persma untuk menciptakan internet damai? Penelitian dilakukan pada delapan perguruan tinggi negeri di Jateng, melibatkan 78 responden. Data dikumpulkan dengan angket kemudian dilakukan analisis regresi ganda. Peran activist persma untuk meluaskan internet damai di kalangan masyarakat luas atau pun di dalam kampus dapat dilakukan dengan bentuk-bentuk seperti: menyiarkan berita secara bertanggung jawab, mengambil sumber-sumber berita yang kredibel, atau dengan memberikan pendampingan pada remaja/ teman sebaya. Pers mahasiswa memiliki kesempatan yang besar untuk menyuarakan internet damai, mendorong para pembaca lebih peduli pada nasib dan masa depan bangsa Indonesia yang plural secara alami untuk terus disatukan dalam Bhinneka Tunggal Ika.